End of enterprise [video cassette] - TV Choice Productions (London TV Choice Productions, 1993)
Summary: This program uses several case studies to examine the legacy of enterprise culture. Case studies include Markham, a manufacturing firm, Derbshire Textiles and a small grocery shop
Colour recording system: PAL
Keywords: Free enterprise -- Great Britain